Phytochemistry of the Aerial parts of Magnolia coriacea collected in Ha Giang, Viet Nam. Issue 5 (31st July 2022) - Ninh, Pham Thi; Dung, Nguyen Thi; Van Loc, Tran; Ha, Chu Thi Thu; Thao, Tran Thi Phuong; Van Chien, Tran
Abstract: Nine compounds, including two sesquiterpenes [((+)‐spathulenol (1 ), caryophyllenol‐II (2 )], five flavonol glycosides [rutin (3 ), quercitrin (4 ), rhamnocitrin 3‐rutinoside (5 ), oxytroflavoside G (6 ), curcucomoside D (7 )], and two hydrocarbons [2‐phyten‐1‐yl‐caprylate (8 ) and tritriacontan‐1‐ol (9 )] were reported for the first time from the leaves and twigs of Magnolia coriacea . Their detailed structures were confirmed by 1D and 2D NMR spectra analyses and compared to the published data. Abstract :